A pocket-factor–triggered conformational switch in the hepatitis B virus capsid - Lecoq, Lauriane (Proc Natl Acad Sci U S A, 2021)
Viral hepatitis is growing into an epidemic illness, and it is urgent to neutralize the main culprit, hepatitis B virus (HBV), a small-enveloped retrotranscribing DNA virus. An intriguing observation in HB virion morphogenesis is that capsids with immature genomes are rarely enveloped and secreted. This prompted, in 1982, the postulate that a regulated conformation switch in the capsid triggers envelopment. Using solid-state NMR, we identified a stable alternative conformation of the capsid. The structural variations focus on the hydrophobic pocket of the core protein, a hot spot in capsid–envelope interactions. This structural switch is triggered by specific, high-affinity binding of a pocket factor. The conformational change induced by the binding is reminiscent of a maturation signal. This leads us to formulate the “synergistic double interaction” hypothesis, which explains the regulation of capsid envelopment and indicates a concept for therapeutic interference with HBV envelopment.